2019
DOI: 10.1055/s-0039-1679901
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-Cardiolipin and Anti-β2glycoprotein I Antibodies Differs between Platforms without Influence on Association with Clinical Symptoms

Abstract: Background The anti-phospholipid syndrome (APS) is characterized by thrombosis and/or pregnancy morbidity with persistent presence of anti-phospholipid antibodies (aPL). Laboratory criteria include aPL detection by coagulation tests for lupus anticoagulant (LAC) or solid phase assays measuring anti-β2 glycoprotein I (aβ2GPI) or anti-cardiolipin (aCL) immunoglobulin (Ig) G/IgM antibodies. External quality control programs illustrate that commercially available aPL assays produce variable results. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 31 publications
(60 reference statements)
1
66
1
Order By: Relevance
“…Automated systems limit the intralaboratory and interlaboratory variation for one system 36 . We have recently shown that with commercially available solid‐phase assays, even with eliminating interlaboratory and interoperator variation, there is still variable detection of aCL and aβ2GPI IgG/M between platforms 32 . In this study, a discrepancy of 36%, 60%, 53%, and 36% for aCL IgG, aCL IgM, aβ2GPI IgG, and aβ2GPI IgM positivity was observed, respectively.…”
Section: Anticardiolipin and Antibeta2‐glycoprotein I Antibodiesmentioning
confidence: 59%
See 3 more Smart Citations
“…Automated systems limit the intralaboratory and interlaboratory variation for one system 36 . We have recently shown that with commercially available solid‐phase assays, even with eliminating interlaboratory and interoperator variation, there is still variable detection of aCL and aβ2GPI IgG/M between platforms 32 . In this study, a discrepancy of 36%, 60%, 53%, and 36% for aCL IgG, aCL IgM, aβ2GPI IgG, and aβ2GPI IgM positivity was observed, respectively.…”
Section: Anticardiolipin and Antibeta2‐glycoprotein I Antibodiesmentioning
confidence: 59%
“…aCL detection can confirm the positivity of aβ2GPI. Positivity of aCL without aβ2GP positivity should be interpreted with caution, since both parameters correlate well and discrepant results sometimes result from the use of assays from different manufacturers 12,32 …”
Section: Anticardiolipin and Antibeta2‐glycoprotein I Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, we hypothesized that the added value of the anti‐DI IgG assay measured by QUANTA Flash ® depends on the platform used to detect anti‐β2GPI and anti‐CL IgG. This hypothesis comes from our previously published results demonstrating a variable exposure of the G40‐R43 epitope on domain I of β2GPI coated in the different commercially available anti‐CL and anti‐β2GPI assays . In this multicenter study, we therefore determined the added value of anti‐DI testing to the current APS classification criteria, when anti‐CL and anti‐β2GPI were measured by four different commercially available assays.…”
Section: Discussionmentioning
confidence: 99%